Germination, Growth, Chlorophyll Fluorescence and Ionic Balance in Linseed Seedlings Subjected to Saline and Alkaline Stresses - Rui Guo; Ji Zhou; WeiPing Hao; FengXuex Gu; Qi Liu; HaoRu Li; Xu Xia; LiLi Mao (Plant Production Science, 2014)
Both saline and alkaline stresses involve osmotic stress and ion injury; however, alkaline stress involves the stress due to a high pH. The aim of this study was to evaluate the physiological responses of linseed seeds and seedlings to saline and alkaline stresses and to elucidate the adaptive mechanisms involved. Stresses were generated by exposure to neutral saline solutions of saline stress and alkaline stress for 7 days. The relative growth rate (RGR) and water content (WC) of linseed seedlings were scarcely affected by salinity stress, but significantly reduced by alkaline stress. Photosynthetic activity and pigment indices were hardly changed under saline stress but were inhibited by alkaline stress. This implies that alkaline stress may be mediated by Na+ uptake and accumulation up to toxic levels, leading to a decrease in photosynthetic pigments and damage to the photosynthetic apparatus. Alkaline stress causes precipitation of phosphate and metal ions which causes a sharp decrease in ionic activity and in the concentrations of various other ions. The results indicated that carbohydrates and proline synthesis decreased osmotic potential, remedied the shortage of inorganic anions and maintained stability of the intracellular pH allowing the plant to cope with osmotic stress from a high Na+ vacuolar concentrations. However, the contribution of betaine to osmotic adjustment was small in linseed seedlings. With increasing solution concentrations, the rate of germination of linseeds was more severely inhibited under alkaline stress than under saline stress.